PENGARUH STRUKTUR MODAL DAN GROWTH OPPORTUITY TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHU 2009-2014 - Dewi, Anisfu Sari; ", Ruzikna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This study aims to simultaneously and simultaneously influence the capital structure and growth opportunities against the company. Where independent variable in this research is capital structure and growth of opportunity depend variable dependent company. The sample used is secondary data derived from the financial statements of telecommunication companies listed on the Indonesia Stock Exchange (BEI) in 2009 to 2014.This study uses secondary data from the company's financial statements. Samples and sampling using census techniques. Classic test in trial. Classical correlation test, multicolinearity test, heterokedastisity test and autocorrelation test. Data analysis using multiple linear regression analysis, t test, F test, and test of determination. Data analysis using multiple linear regression analysis with SPSS 20.The results of this study indicate the relationship between the company, while the variable growth of business opportunities to companies engaged in the Indonesia Stock Exchange. The simultaneous test results (f) show the effect of capital and growth on the companies that are in Indonesia Stock Exchange.Keywords: capital structure, growth opportunities and value company